Trends and synchrony in fluctuations of the numbers of Whinchat (Saxicola rubetra) and European Stonechat (S. rubicola) in chalk steppe of North-eastern Ukraine - Banik, M. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The problem of coexistence of related species within the same communities poses a question of how similar are the fluctuations of their numbers. Whinchat (Saxicola rubetra) and European Stonechat (S. rubicola) is an example of such a pair of phylogenetically related bird species, which are members of a foraging guild of sit-and-wait insectivores in open habitats. In Ukraine both species are quite common in meadows, steppes, fallow lands and other grassland habitats including undisturbed areas in nature reserves. In North-eastern Ukraine Whinchat and European Stonechat are characteristic of the bird communities of hills with chalk outcrops where they represent a group of species linked to chalk steppe. The trends in numbers and synchrony in fluctuations in the numbers of both species in this habitat were studied in national nature park ‘Dvorichanskyi’, Kharkiv region, North-eastern Ukraine for 9 years’ period (2010–2018). The data were retrieved from the results of yearly monitoring bird counts in chalk grassland habitats. The total-area census method was used on 3 plots of unequal size (17.8, 33.2, and 41.0 ha). The trends were analysed in programme TRIM (TRends & Indices for Monitoring data) vers. 3.53. The extent of synchrony was estimated by means of zero-lag cross-correlation between the time series of log-transformed growth rates. Additionally, the coincidence of the direction of changes and the coincidence of peaks in series were checked. The trend in Whinchat abundance is characterised as significant steep decline (multiplicative slope 0.840, standard error 0.03; p<0.01). The trend in European Stonechat abundance is classified as non-significant uncertain (multiplicative slope 0.909, standard error 0.06). The trends in both species correspond to general trends in Europe evidenced in PanEuropean Common Bird Monitoring Scheme for 1980–2016 and 1989–2016 for Whinchat and European Stonechat accordingly. The synchrony in fluctuations of the numbers of Whinchat and European Stonechat in chalk steppe habitats proved to be weak. Time series of both species abundances run in different directions almost in all cases where the comparison was possible that indicates probable differences in the causes of the dynamics of their populations. The study prompts to launch new or extend existing monitoring schemes in nature reserves and national parks in Ukraine to get reliable estimates for the trends in numbers of both rare and common bird species.